AN OVERVIEW OF DENGUE HEMORRHAGIC FEVER CASES AND ENVIRONMENTAL FACTORS IN SUMENEP DISTRICT IN 2018 - Ainun Jaria; Chatarina Umbul Wahjuni (Jurnal Berkala Epidemiologi, 2020)
Background: Dengue hemorrhagic fever (DHF) has been occurring in Indonesia for more than 50 years, and there were 65,602 cases of it in 2018 alone. Sumenep District reported the 12th highest number of DHF cases (292) in East Java Province in 2018. Purpose: This research aims to describe DHF in Sumenep District in 2018. Methods: This research is a descriptive study employing a cross-sectional design. The data used in this research were secondary data gathered from the Sumenep Health Office in 2018. The variables observed in this research were the epidemiological characteristics included in the epidemiological triangle—people, place (region), and time. Descriptive analysis was conducted to examine the DHF case distribution, using a frequency table, among the people, place (region), and time variables. Results: Sumenep District is home to 1,085,227 citizens, with a population density of 518 people/km2. The number of DHF cases in Sumenep District was 292, with the highest concentration of cases in the age range of 5–14 years (47.30%); the most cases were also male (57.19%). DHF often occurred in sub-districts with high population density, and more commonly in January. Conclusion: Most of the Sumenep District’s DHF cases in 2018 were males in the age group of 5–14 years old.